Real-world cost-effectiveness of nirmatrelvir-ritonavir as treatment for SARS-CoV-2 infection in the Belgian setting with omicron variant - Marbaix, Sophie; Simoens, Steven; Clevenbergh, Philippe; Van Bleyenbergh, Pascal; Liberman, Keliane; Dehenau, Dimitri (Frontiers in Public Health, 2025)
BackgroundNirmatrelvir-ritonavir is an oral treatment for SARS-CoV-2 infection in patients who are at high risk of developing severe COVID-19 disease. This antiviral has proven to significantly reduce the risk of hospitalization and death compared to no anti-SARS-CoV-2 treatment in this target population. This paper aims to assess the cost-effectiveness of nirmatrelvir-ritonavir in Belgium using real-world evidence.MethodsA static decision tree model was developed to capture the health progression of patients infected with the SARS-CoV-2 virus. Outcomes were expressed in Quality Adjusted-Life Years (QALYs), hospitalizations, Intensive Care Unit (ICU) admissions, deaths and Long Covid cases, derived from epidemiological data over the first full year of the Omicron variant’s circulation (2022). Costs were calculated for the year 2023 from the healthcare payer’s perspective. Extensive sensitivity analyses were conducted to test the robustness of the cost-effectiveness results.ResultsIn a cohort of 1,000 patients, treatment with nirmatrelvir-ritonavir is projected to save 95 QALYs and €82,658 compared to no anti-SARS-CoV-2 treatment over a lifetime horizon. These savings primarily stem from the reduction in hospitalizations among vulnerable patients who typically require a longer recovery time. The analysis also indicates 5 fewer ICU admissions and 8 fewer premature deaths per 1,000 infected patients.ConclusionIn the context of Omicron SARS-CoV-2 infection, administering nirmatrelvir-ritonavir to patients at high risk of severe disease improves health outcomes and reduces costs. Nirmatrelvir-ritonavir is 100% likely to be cost-effective at a willingness to pay of €2,000 per QALY.